J. D. Rolleston (1873–1946): An Overlooked Scholar of Folk Medicine. Issue 1 (2nd January 2017) - Miller, Stephen
Abstract: J. D. Rolleston was a medical doctor of considerable renown and skill whose scholarly interests in retirement included the study of folk medicine. He authored some seventeen papers on the topic, which are the subject of an annotated bibliography here, together with a short note on his professional life.